1981
DOI: 10.1152/ajpregu.1981.241.1.r72
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced eating in rats

Abstract: Mild tail pinch (TP) in rats resulted in 72% of animals displaying ingestive behavior with 20% demonstrating gnawing behavior without food ingestion and 8% demonstrating licking behavior only. The animals ate steadily over 5 min with a maximum rate occurring at 1 min (0.5 +/- 0.2 g). There was a circadian rhythm of TP-induced behavior with the peak food ingestion occurring at 24 h. A mild increase in blood glucose occurred 120 s after commencement of TP (115 +/- 4 mg/dl). Common satiety signals such as stomach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 0 publications
2
53
1
1
Order By: Relevance
“…Currently, there are controversies about stress and food intake, and literature shows that chronic stress may lead, in some cases, to increased intake, but mainly to decrease of calorie intake, and consequently, loss of body weight (18). The link between stress, food intake, and weight loss has been used as a reliable marker to assess the severity of the stress model.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are controversies about stress and food intake, and literature shows that chronic stress may lead, in some cases, to increased intake, but mainly to decrease of calorie intake, and consequently, loss of body weight (18). The link between stress, food intake, and weight loss has been used as a reliable marker to assess the severity of the stress model.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been suggested that, as behaviors associated with feeding are incompatible with defensive behaviors, those systems associated with reductions in consummatory behavior should be linked directly or indirectly to those subserving stressor reactivity (Akana et al 1994;Dallman et al 1995;Merali et al 1998;Pecoraro et al 2004). In support of this contention, it is not only well-documented that stressor exposure alters food intake (Levine and Morley 1981;Morley et al 1983;Marti et al 1994;Valles et al 2000;Tamashiro et al 2007), but that appetitive stimuli influence the stress response including the secretion of glucocorticoids (Follenius et al 1982;Al-Damluji et al 1987;Karbonits et al 1996;Piazza and Le Moal 1997;Merali et al 1998). Moreover, several investigators have reported that the state of hunger (fasting vs. satiated) as well as the type of meal consumed (high vs. low fat content) influences the responsiveness of the hypothalamic-pituitary-adrenal axis to stressor exposure (Shiraishi et al 1984;Schwartz et al 1995;Dallman et al 1995;Leal and Moreira 1997;Tannenbaum et al 1997).…”
Section: Introductionmentioning
confidence: 85%
“…Stress-induced eating and defecation occur across species and can be triggered by exposure to a painful stimulus (1)(2)(3)(4). Yet, very little is known about the effects of feeding (eating and drinking), micturition, and defecation on pain sensitivity.…”
mentioning
confidence: 99%